Om at tilskrive sig Troens rare klenodie - Egebak, Niels (Grundtvig-Studier, 1971)
On writing in order to obtain the Rare Jewel of Faith By Niels Egebak This ‘reading5 of one of Grundtvig5s most well known and best loved hymns, ‘Hil dig Frelser og Forsoner5 is an example of a technique of interpretation that looks upon Grundtvig5s original text from ‘Sangværk til den danske Kirke5 ( 1837) as a text ‘here and now5, as if it were ‘printed in this year5, and as an integrated part of the corpus of texts that forms part of our total surroundings. By way of introduction the concept of tradition laid down by T. S. Eliot is referred to. In ‘Tradition and the Individual Talent he claims that with each new work the total tradition should be modified if, instead of perishing, it is to incorporate the new additions. It is pointed out that the present version of the official hymn book has left out st. 2- 4, which gives rise to the suspicion that the abbreviation may be due to ideological considerations. Further, that the first half of the text is closer to the latin original than st. 7- 12, and an attempt is made to demonstrate that Grundtvig5s text emphasises the subjective rather than the objective aspect, and that this may be connected with he function of obtaining atonement that the text seems to have. The way to faith, or to a retrieval of faith, goes through a confrontation with the Passion, which is not to be understood, but to be accepted as the cause of redemption. In the original text this confrontation is of a completely personal nature; it is undertaken by the poet5s ‘I5, and this I places itself in a position of opposition to the world and other people. The recognition of the opposition between Christ's mysterious, self-sacrificing love and the poet's own scruples makes him pray the crucified Christ to help him back to the straight way; this transforms his belief in Christ5s presence to him into certainty, and he is inspired with confidence that, in due course, Christ will take him by the hand and lead him to Paradise.—In other words, the text deals with its own process of creation. Or rather: it is writing in order to obtain ‘The rare Jewel of Faith5 (Brorson); but is this not what all authentic hymn writing is?